EVALUATION OF ADHESIVE AND COMPRESSIVE STRENGTH OF GLASS IONOMER CEMENTS - Salimov Odilhon Rustamovich; Melikuziev Tukhtasin Sherkuzievich (Scholar Express Journals, 2025)
The study aimed to evaluate the adhesive and compressive strength characteristics of glass ionomer cements (GICs), which are widely used in modern dentistry. The research investigated various commercially available GIC formulations through standardized laboratory testing procedures. Adhesive strength was measured using shear bond strength tests on prepared dental surfaces, while compressive strength was evaluated through standardized compression testing protocols. The results demonstrated significant variations in both adhesive and compressive properties among different GIC formulations. The findings provide valuable insights for clinical applications, helping practitioners make informed decisions when selecting appropriate glass ionomer cements for specific dental procedures. This research contributes to the understanding of mechanical properties of dental materials and their optimal utilization in restorative dentistry.
Keywords: glass ionomer cements; adhesive strength; compressive strength